Education, material condition and physical functioning trajectories in middle-aged and older adults in Central and Eastern Europe: a cross-country comparison - Hu, Yaoyue; Pikhart, Hynek; Pająk, Andrzej; Kubínová, Růžena; Malyutina, Sofia; Besala, Agnieszka; Peasey, Anne; Marmot, Michael; Bobak, Martin (Journal of epidemiology and community health, 2016)
BACKGROUND: Two competing hypotheses, cumulative advantage/disadvantage and age-as-leveller, have been proposed to explain the contradictory findings on socioeconomic differences in health over the lifespan. To test these hypotheses, this investigation examined the influence of educational attainment and material condition on individual trajectories of physical functioning (PF) in unexplored ageing populations in Central and Eastern Europe. METHODS: 28 783 men and women aged 45-69 years selected from populations in seven Czech towns, Krakow (Poland) and Novosibirsk (Russia). PF was measured by the Physical Functioning Subscale (PF-10) of the Short-Form-36 questionnaire (SF-36) at baseline and three subsequent occasions. The highest educational attainment was self-reported at baseline, and material condition was captured by the sum score of 12 household amenities and assets. RESULTS: In all cohorts, participants with a university degree had the highest PF-10 score at baseline and slowest rate of decline in the score during follow-up, while the lowest baseline scores and fastest decline rate were found in participants with less than secondary education in all cohorts and in Russians with secondary education. Similar disparities in the baseline PF-10 score and decline rate were observed across tertiles of material condition, but differences in decline rates across the three tertiles among Czechs or between the lower two tertiles among Russians were not statistically significant. CONCLUSIONS: Disparities in PF by educational attainment and material condition among middle-aged and older adults in Central and Eastern Europe existed at baseline and widened during ∼10 years of follow-up, supporting the cumulative advantage/disadvantage hypothesis.
Keywords: společenská třída; senioři; Poland; PHYSICAL FUNCTION; Russia; senioři nad 80 let; Česká republika; Social Class; Rusko; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Cohort studies; sociální determinanty zdraví; stupeň vzdělání; Polsko; Czech Republic; kvalita života; Social Determinants of Health; LONGITUDINAL STUDIES; Aged, 80 and over; ženské pohlaví; Humans; Surveys and Questionnaires; Health inequalities; lidé středního věku; Epidemiology of ageing; Educational Status; Female; Aged; Quality of Life; lidé; Male